Forecasting the economic consequences of COVID-19 on longstanding illnesses in Wales. (20th October 2021) - Kadel, R; Allen, J; Dyakova, M; Bellis, M
Abstract: Introduction: The unemployment rate following the COVID-19 pandemic in Wales is increasing and there is a positive link between unemployment and longstanding illnesses. This study aimed to project the percentage of adults with longstanding illnesses and chronic health conditions following COVID-19 associated with the economic consequences. Methods: We retrieved historical data on the unemployment rates and status of longstanding illnesses among adults from the Office for National Statistics (ONS) and National Survey for Wales (NSW), and used time-series models to project the unemployment rates and percentage of adults with longstanding illnesses and chronic health conditions over a three year period (2020/21 - 2022/23). Results: Without reparative interventions, the unemployment rate is expected to increase sharply from 3.8% in 2019 to about 7% in 2020 following COVID-19 and then gradually increase over the projected period. With increased unemployment, longstanding illness (LSI) would be expected to increase gradually following COVID-19, with an estimated increase of around or exceeding 4% over three years depending on the LSI measure. There would be a higher increment in the percentage of adults with limiting LSI compared with adults with any LSI, suggesting implications for wider health and social care services. With current unemployment predictions, the percentage of adults with chronic health conditions is projected to increase following the COVID-19 pandemic over the projected period, with a higher increment for mental health and endocrine/metabolic conditions Conclusions: The longstanding illnesses and chronic health conditions are expected to increase in the coming years following COVID-19 pandemic. Therefore, preventative measures for longstanding illnesses and chronic health conditions should be a priority for a sustainable recovery from the COVID-19. Key messages: Without reparative interventions, the unemployment rate is expected to increase following the COVID-19 pandemic. The projected prevalence of limiting longstanding illness in adults following COVID-19 suggests implications for wider health and social care services.